Research of professional values based on methods «Square of values» (Pedagogy of Higher and Secondary Education, 2014)
Murzina O. A. Research of professional values based on methods «Square of values»The research methodology of individual’s value orientations based on the method «Square of values» has been considered in the article. The concept of «professional value orientations» means for us the orientation of the personality on goals, means and conditions of professional activity. Particular attention is focused on the questionnaire of cadets and students of Zaporozhye Law Institute DDUVS. As a result of research, we came to the conclusion that the proposed testing methodology has an effective instrument for the study of professional value orientations of future specialists.
Keywords: values; values based; professional values; professional values based; professional occupation; «Square of values»